The Impact of Mass Exodus on the Resurgence of COVID-19 Cases: Case Study of Regions in Indonesia - Aini, Wirdatul; Sukandar, Kamal Khairudin; Nuraini, Nuning; Handayani, Dewi (Frontiers in Applied Mathematics and Statistics, 2022)
Consideration of human mobility is essential for understanding the behavior of COVID-19 spread, especially when millions of people travel across borders around Eid al-Fitr. This study aims to grasp the effect of mass exodus between regions on active cases of COVID-19 through a mathematical perspective. We constructed a multiregional SIQRD (susceptible–infected–quarantined–recovered–death) model that accommodates the direct transfer of people from one region to others. The mobility rate was estimated using the proposed Dawson-like function, which requires data from an origin–destination matrix. Assuming that only susceptible, inapparently infected, and recovered individuals travel around Eid al-Fitr, the rendered model well-depicted the actual data at that time, giving either a significant spike or decline in the number of active cases due to the mass exodus. Most agglomerated regions such as Jakarta and Depok City experienced a fall in active case numbers, both in actual data and in the simulated model. However, most rural areas experienced the opposite, such as Bandung District and Cimahi City. This study confirmed that most travelers journeyed from big cities to the rural regions, and it scientifically demonstrated that mass mobility affects COVID-19 transmission between areas.